2015
DOI: 10.1242/jeb.106369
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hypometabolism: insights into epigenetic controls

Abstract: For many animals, survival of severe environmental stress (e.g. to extremes of heat or cold, drought, oxygen limitation, food deprivation) is aided by entry into a hypometabolic state. Strong depression of metabolic rate, often to only 1-20% of normal resting rate, is a core survival strategy of multiple forms of hypometabolism across the animal kingdom, including hibernation, anaerobiosis, aestivation and freeze tolerance. Global biochemical controls are needed to suppress and reprioritize energy use; one suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 97 publications
3
131
0
Order By: Relevance
“…Consistent with [8], this finding likely reflects metabolic changes mediated by O 2 sensors that drive the shift of the redox cellular status of NADH to a more reduced form with a rapid recycling of NAD + to NADH. Certainly, hypoxic situations must improve and adjust the metabolic and O 2 -carrying capacities of challenged fish to cope and reach internal homeostasis [29]. The trigger observed in plasma antioxidant capacity after acute and severe hypoxia demonstrates a general decrease in metabolic rates that also reflects the aerobic/anaerobic shift of metabolism [25, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with [8], this finding likely reflects metabolic changes mediated by O 2 sensors that drive the shift of the redox cellular status of NADH to a more reduced form with a rapid recycling of NAD + to NADH. Certainly, hypoxic situations must improve and adjust the metabolic and O 2 -carrying capacities of challenged fish to cope and reach internal homeostasis [29]. The trigger observed in plasma antioxidant capacity after acute and severe hypoxia demonstrates a general decrease in metabolic rates that also reflects the aerobic/anaerobic shift of metabolism [25, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have identified diverse functions for protein deacetylases in the control of eukaryotic gene expression and cellular metabolism, including potential roles in transcriptional suppression previously implicated for Class I and II deacetylases (also known as histone deacetylases or HDACs) in the context of mammalian hibernation [30,41] and turtle anoxia tolerance [22,41]. Previous studies also hypothesized a possible role for SIRT deacetylases in the regulation of the major metabolic changes that occur over the hibernation torpor-arousal cycle, with pathways of lipid catabolism, oxidative stress resistance, and transcriptional suppression being likely candidates for regulation by SIRTs [28,32].…”
Section: Introductionmentioning
confidence: 99%
“…Acetylation is rapidly emerging as a key mechanism that regulates the expression of numerous genes (epigenetic modulation through activation of nuclear histone proteins), as well as functions of multiple cytoplasmic proteins involved in key cellular functions such as cell survival, repair/healing, metabolism, signaling, and proliferation (3, 8, 9). It has been reported that, at the molecular level, hemorrhage leads to an imbalance in acetylation of proteins (hypo-acetylation of proteins compared to the normal state) and that treatment with histone deacetylase (HDAC) inhibitors can promptly restore the balance (10).…”
Section: Introductionmentioning
confidence: 99%